A autonomia da vontade na doação de órgãos post mortem: o cinema como via de reflexão para biodireito - Santos, Márcio dos (2024)
The dissertation aims to discuss the autonomy of the individual in the bioethical context of postmortem organ donation. With this aim, it brings to reflection, at an interdisciplinary level, the relationship established in the field of biolaw, with cultural contributions evidenced by cinema. It contextualizes, through filmic discourse, the complex dilemma between the protagonism of the individual's decision and family legitimacy regarding the availability of the body in postmortem procedures. In this context, the role of the living will as a mechanism for consolidating the subject's autonomy is discussed, given that it is configured as a means of expressing personal will for post-mortem organ donation. This discussion is in line with the current Civil Code, but is at odds with the restrictive interpretation of Law 9434/97, which deals with organ donation and transplants and gives the family the power to decide on the fate of deceased relatives' organs. Faced with this problem, we resort, through bibliographical and jurisprudential research, to a phenomenological methodology with a qualitative approach in which organ donation starts to be seen in its jus-cultural aspect, provided by film analysis. In this way, interdisciplinarity with cinematographic art seeks ways to problematize and democratize the cultural and constitutional aspects of bioethical autonomy. Finally, the importance of addressing this issue is highlighted, given the nature of post-mortem organ donation being guided by alterity, empathy, solidarity, a sense of perpetuation of life, in which it is necessary to implement the bioethical principles of autonomy, beneficence, non-maleficence and justice.